Changing the treatment paradigm for Parkinson's disease psychosis with pimavanserin. Issue 7 (3rd July 2019) - Lyons, Kelly E.; Pahwa, Rajesh; Hermanowicz, Neal; Davis, Thomas; Pagan, Fernando; Isaacson, Stuart
ABSTRACT: Introduction : Parkinson's disease psychosis (PDP) may affect up to 60% of patients with Parkinson's disease over the course of their disease, and is associated with poor prognosis, including increased risks of mortality and nursing home placement. PDP treatments have been limited to off-label use of atypical antipsychotics, most of which pose risks of worsened motor symptoms and other potential adverse events (AEs) due to their dopamine receptor blockade and additional off-target receptor affinities. Pimavanserin is a highly selective 5-HT2A inverse agonist and poses no known risks for worsening of parkinsonism or other off-target receptor AEs. Pimavanserin is the first and only medication approved for PDP treatment. Areas covered : This review covers estimated prevalence, clinical characteristics, diagnostic criteria, and risk factors for PDP; the hypothetical progression of PDP; management of PDP including use of antipsychotics; pharmacology and clinical trial data on pimavanserin; and expert opinion on PDP treatment. The NLM/PubMed database was searched for papers using the search terms of "PDP" AND "treatment" AND "pimavanserin" for the last 10 years. Expert opinion : The recent insights into PDP pathophysiology and approval of the only medication specifically to treat PDP are key advances that should improve the recognition, diagnosis, and management of PDP.